Inclusive Da'wah and Social Transformation: Conceptualizing Islamic Communication from Lombok for Indonesia - Lalu Ahmad Zaenuri (Lembaga Bale Literasi, 2025)
This study examines inclusive da'wah (Islamic outreach) as a transformative model of Islamic communication in Lombok, West Nusa Tenggara, Indonesia. In an era marked by religious polarization and identity politics, inclusive da'wah emerges as a counternarrative that prioritizes dialogue, cultural adaptation, and social solidarity over exclusionary sectarian approaches. This research employs a qualitative phenomenological design with ethnographic elements, conducted across multiple sites in Lombok over a twelvemonth period (January-December 2023). Data were collected through semi structured interviews with 18 key informants including da'i, pesantren kyai, community leaders, and lay participants complemented by participant observation at 24 da'wah gatherings and systematic document analysis. Thematic analysis following Braun and Clarke's six phase framework was applied to identify patterns across the data corpus. Findings reveal three interconnected dimensions of inclusive da'wah in Lombok: (1) a culturally embedded communicative practice integrating Sasak cosmological values with Islamic pedagogical traditions; (2) a social transformation mechanism through which da'wah networks catalyze community empowerment, educational access, and interfaith coexistence; and (3) a reconceptualized model of Islamic communication that moves beyond transmission toward dialogical encounter. The study introduces the concept of dakwah perjumpaan as an analytical framework bridging Habermasian communicative rationality, the philosophy of encounter developed by H.M. Husni Muadz, and Islamic communication theory. This Lombok model offers replicable principles for inclusive religious communication in Indonesia's pluralist national context, with implications for da'wah training programs, the Moderasi Beragama policy agenda, and communitybased conflict prevention initiatives.